Serum biomarkers for differential diagnosis of adnexal masses in pregnant and nonpregnant women - S A Martynov (IP Berlin A.V., 2014)
The literature review is devoted to evaluation of possibilities of serum biomarkers and their combinations in differential diagnosis of benign and malignant adnexal masses in pregnant and nonpregnant women.